Implementasi Profil Pelajar Pancasila Dalam Pembentukan Karakter Siswa Di Sma Darut Taqwa - Mohammad Debi Wananda (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines how the Pancasila Student Profile is implemented to shape student character at Darut Taqwa High School. The objective of the study is to describe its implementation, reinforcement methods, and supporting and inhibiting factors. This study employed a qualitative descriptive approach. Data were collected from the principal, P5 teachers, and students through interviews, observations, and documentation. Data analysis was conducted in stages and validated through triangulation of sources, data, and methods. The results indicate that P5 implementation is carried out through positive habits and religious activities. Character strengthening methods include integrating P5 into lessons, fostering discipline, and the role of teachers as role models. Supporting factors include the legal basis, the role of teachers, and the P5 curriculum, while inhibiting factors include student fatigue, limited time and funding, and lack of student enthusiasm.